Influence of Instrument design on Post endodontic pain in Single visit Root canal treatment using PTN and MTWO Rotary systems in Asymptomatic irreversible pulpitis of Multirooted teeth- A Randomized Clinical Trial - Surada, Ramakrishna; Podugu, Uday Kumar; Agarwal, Pamita; Sonawane, Asmita Ashok; D. Khanvilkar, Unmesh; Grandhi, Nishita (Journal of Neonatal Surgery, 2025)
Aim: The aim and objective of the present randomized clinical trial is to evaluate the incidence of post operative pain after single-visit root canal treatment using two different rotary systems namely Protaper Next and M two in multi rooted teeth. Materials and Methods: 40 adult subjects with multi rooted teeth diagnosed as asymptomatic irreversible pulpitis were randomly assigned into two groups. The teeth were instrumented using Protaper Next and M two rotary systems. Post operative pain was evaluated using Modified Verbal Descriptor Pain Scale at 8hr, 24hr, 48hr and 72hr. Results: Data analysis was carried out using the Statistical Package for Social Sciences (SPSS version21). Pair wise comparisons at different intervals was made using Mann-Whitney test. There is lower incidence of post operative pain in both the groups and the difference was not statistically significant (p>0.05). Conclusion: Both Protaper Next and M two do not cause post operative pain while treating asymptomatic irreversible pulpitis in multirooted teeth. Both the files can be used for single visit endodontic procedures effectively